LANGUAGE CHANGE AS A MATTER OF FACT - Abdul Halim (Shautut Tarbiyah, 2011)
All physical aspects of the universe and all aspects of human life aresubject to change, and languages are no exception. Indeed, “one ofthe eternal truths about living languages is that they all change”(Winkler, 2007, p. 197). Individual changes can be quite abrupt andobvious, as when new words make an appearance and becomepopular. Normally, however, language change is gradual, almostimperceptible. In fact, its speakers are usually unaware of thechanges as they are occurring, as with the slow alteration inpronunciation when one generation speaks slightly different fromanother. In light of this, in the majority of cases, language change isthe consequence of changes in the socio-political structure of aparticular population.Key Words: language, change, socio-political structure